THE INFLUENCE OF ORGANIZATIONAL CULTURE ON ACCOUNTING PROFESSIONAL ETHICS - Damayanti, Santi Adella (Journal Accounting International Mount Hope, 2025)
The purpose of this study is to analyze the influence of organizational culture and accounting professional ethics on employee performance. Organizational culture plays a crucial role in a company because it motivates employees to work and, in conjunction with employee work ethic, improves employee performance. Accounting ethics, along with ensuring the protection and fairness of reporting, preventing fraud, and increasing public trust in the accounting profession. By applying the principles of accounting ethics and organizational culture, we aim to create a business environment based on transparency and integrity.